Determinaton of Volatile Aroma Components of Gyromitra Mushroom Using Headspace Gas Chromatography Mass Spectrometry (HS-GC/MS) - Hatıra Taşkın; Gökhan Baktemur; Ebru Kafkas; Saadet Büyükalaca (Turkish Journal of Agriculture: Food Science and Technology)
Gyromitra is one of the poisonous mushrooms with being evaluated as edible mushrooms in Turkey and in many countries. This study was performed to determine volatile aroma compounds of Gyromitra collected from Turkey at Horticulture Department of Çukurova University, Adana-Turkey in 2011. Gyromitra mushroom samples collected from Adana province of Turkey were used as material. Volatile aroma compounds were determined using Headspace Gas Kromotografi Mass Spectrometry (HS-GC/MS) technique. Twenty-four different volatile aroma compounds were detected in this study. Phenol was identified as the major aroma component at 47.10% content. This compound was followed with Carbamic acid methyl ester (14.12%), Acetic acid (4.47%), 1-Octen-3-ol (4.14%) and Acetaldehyde (4.10%). Phenol is an antioxidant compound and it has anti-carcinogenic effect. 1-Octen-3-ol is an alcohol which commonly found in mushroom. Acetic acid and Acetaldehyde are poisonous compounds. Although high number of phenol and 1-Octen-3-ol in Gyromitra fungus is displayed as flavor and significant in terms of health, containing toxic compounds such as acetic acid and the acid aldehyde raises the risk factors in exhaustion.